2013
DOI: 10.5812/numonthly.15292
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular Anterior Nutrient Canals in Periapical Radiography in Relation to Hypertension

Abstract: Background:Hypertension (HTN) is the most commonly encountered systemic disease in general population. Nutrient canals contain blood vessels and nerves that mostly appear in the anterior mandibular region. Nutrient canals are not detected in radiographs of all patients, and their normalcy is controversial by many investigators.Objectives:The present study investigated the correlation between the appearance of nutrient canals and hypertension as a potential clue to diagnose patients with hypertension.Patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In a posterior study, Przystańska and Bruska [18] confirmed the presence of the mylohyoid nerve, sublingual artery, and accompanying vessels in these foramina through histological examination. Abdar-Esfahani and Mehdizade [19] carried out a study on mandibular anterior nutrient canals using periapical radiography in relation to hypertension. The incidence of anterior nutrient canals was 37.5 % in patients with hypertension and 53.1 % in subjects without hypertension, but the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…In a posterior study, Przystańska and Bruska [18] confirmed the presence of the mylohyoid nerve, sublingual artery, and accompanying vessels in these foramina through histological examination. Abdar-Esfahani and Mehdizade [19] carried out a study on mandibular anterior nutrient canals using periapical radiography in relation to hypertension. The incidence of anterior nutrient canals was 37.5 % in patients with hypertension and 53.1 % in subjects without hypertension, but the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%